2021
DOI: 10.21608/ejchem.2021.55840.3199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Hepato- and Neuroprotective Effect of Chemical Constituents in Saussurea costus Extract Against the Toxicity Induced by Chloropyrofos Ethyl in Rats

Abstract: The health hazardous occurred in both human and animals as a result of the continuous misuse of pesticides drives the researchers for looking about the solution. Natural plant extracts contain active phyto-constituents with antioxidant potency enables them to inhibit production of the free radicals that induce damage of the cells. The present study aimed to reveal efficiency of Saussurea costus (S. costus extract) against the hepato-and neurotoxicity induced by Chloropyrofos ethyl (CPF) in experimental animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…It was suggested that the elevation in the activities of these aminotransferases might be probably because of the toxic impact on the cell membranes of hepatocytes where petroleum hydrocarbons were oxidized into free radicals or reactive intermediates (Nwanjo and Ojiako, 2007). Interestingly, treatment of the leukemic rats with SEE exhibits an ameliorative effect against the benzene resultant-hepatotoxicity, this effect was achieved from the marked lowering potential of these aminotransferases activities; This result concomitant with some previous studies (Deabes et al 2021;Ashry et al 2022 ), and may be due to the antioxidant potential of SEE-included phytochemical compounds, such as flavonoids and chlorogenic acid, which act as antioxidant agents and led to stabilization of the lipid peroxidation resultant free radicals, consequently preventing benzeneinduced hepato-toxicity (Shabnam et al, 2018). Otherwise, a significant extra increase in the activity of serum ALAT and ASAT in the CP-treated leukemic animals' group was observed compared with the inducedleukemic animals' group; these findings are consistent with Abdel- Wahhab et al, (2021) who found that CP-injection induced significant elevations in serum ASAT and ALAT activities; the excessive elevation of ASAT and ALAT activity (occurred post CP-treatment of leukemic animals) could be attributed to the excessive oxidative stress that results in inflammation and hepatocellular damage leading to excessive disturbance in the cellular integrity, selective permeability of the hepatocyte membrane, and leakage of these enzymes to the bloodstream (Dang et al, 2008).…”
Section: Resultssupporting
confidence: 79%
“…It was suggested that the elevation in the activities of these aminotransferases might be probably because of the toxic impact on the cell membranes of hepatocytes where petroleum hydrocarbons were oxidized into free radicals or reactive intermediates (Nwanjo and Ojiako, 2007). Interestingly, treatment of the leukemic rats with SEE exhibits an ameliorative effect against the benzene resultant-hepatotoxicity, this effect was achieved from the marked lowering potential of these aminotransferases activities; This result concomitant with some previous studies (Deabes et al 2021;Ashry et al 2022 ), and may be due to the antioxidant potential of SEE-included phytochemical compounds, such as flavonoids and chlorogenic acid, which act as antioxidant agents and led to stabilization of the lipid peroxidation resultant free radicals, consequently preventing benzeneinduced hepato-toxicity (Shabnam et al, 2018). Otherwise, a significant extra increase in the activity of serum ALAT and ASAT in the CP-treated leukemic animals' group was observed compared with the inducedleukemic animals' group; these findings are consistent with Abdel- Wahhab et al, (2021) who found that CP-injection induced significant elevations in serum ASAT and ALAT activities; the excessive elevation of ASAT and ALAT activity (occurred post CP-treatment of leukemic animals) could be attributed to the excessive oxidative stress that results in inflammation and hepatocellular damage leading to excessive disturbance in the cellular integrity, selective permeability of the hepatocyte membrane, and leakage of these enzymes to the bloodstream (Dang et al, 2008).…”
Section: Resultssupporting
confidence: 79%
“…Srinivasan et al (2016) 70 studied the chemical compounds in costus oil and observed that n-hexadecanoic acid to be the major constituent in all examined essential oil accompanied with other fatty acids, hydrocarbons and mono-,di- sesquiterpenes. Recently, Deabes et al (2021) 71 identified 14 components from S. costus ethyl acetate extracts. Compounds like Butanedioic acid and 2TMS derivative were recorded in highest percentage followed by D-(-)-Fructofuranose, pentakis (trimethylsilyl) ether (isomer1), Androstan-17-one, 3-ethyl-3-hydroxy-, (5.alpha.…”
Section: Resultsmentioning
confidence: 99%
“…Sesquiterpene lactones are the most distinctive secondary metabolites of the members of the Compositae (Asteraceae). Several plant families, such as Acanthaceae, Amaranthaceae, Apiaceae, Magnoliaceae, and Costaceae have a diversity of chemical structures and a wide range of biological activities, including antitumourogenic, insect antifeedant, plant growth regulating, antibacterial, antifungal and cytotoxic properties [40,17].…”
Section: Gc-ms Analysis Of S Costus Ethyl Acetate Extractmentioning
confidence: 99%
“…Several biological activities have been reported for plant extracts, which show antiviral, antibacterial and antifungal properties [9][10][11][12]. Medicinal plants, which contain a wide range of phytochemicals are one of the most readily available sources of such compounds [13][14][15][16][17]. Sausurea costus (S. costus) is well known in Islamic medicine, and is recorded in the holy hadiths that Prophet Muhammad (peace and blessings be upon him) said [18].…”
Section: Introductionmentioning
confidence: 99%